THE DEVELOPMENT OF HYPERTENSIVE NEURORETINOPATHY MODEL ON WISTAR RATS - Anna Peresypkina; Alexandr Dolzhikov; Viktoriya Gubareva; Elena Levkova; Anna Shabelnikova (Belgorod National Research University, 2017)
A model of hypertensive neuroretinopathy was developed on Wistar line rats with administration of non-selective NO-synthase blocker N-nitro-L-arginine methyl ester (L-NAME) in a dose 12.5 mg/kg within 28 days on the background of single increased intraocular pressure (IOP) to 110 mmHg. As a result of the interim evaluation of pathology simulation mode the most optimal was a model of hypertensive neuroretinopathy with 5-minute increased IOP at day 26 of the experiment on the background of L-NAME for further study of neuroretinoprotective properties of pharmacological agents. Changes formation of the retina and optic nerve disc (OND), observed in the hypertensive neuroretinopathy, confirmed by ophthalmoscopy, laser Doppler flowmetry (LDF), electroretinography (ERG), histological studies in a group of animals with the pathology modeling at the 29 day of experiment.